2018
DOI: 10.1007/s12282-018-0871-7
|View full text |Cite
|
Sign up to set email alerts
|

Upstaging to invasive ductal carcinoma after mastectomy for ductal carcinoma in situ: predictive factors and role of sentinel lymph node biopsy

Abstract: Routinely performing SLN biopsy for patients undergoing mastectomy for a preoperative diagnosis of DCIS is overtreatment, because the prevalence of SLN metastasis was low. SLN biopsy can be omitted for most patients. In particular, we suggest omitting SLN biopsy for patients who have lesions of ultrasound category 0-3, who have neither a mass nor NMA detected by ultrasound, or whose initial diagnosis was made based on a specimen obtained by methods other than CNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
4
18
3
Order By: Relevance
“…We found the upstage rate to invasive carcinoma to be 29%. This is consistent with the reported 8%‐40% upstage rate and corresponds with Brennan et al's meta‐analysis which found 26% (95% CI: 23%‐30%) of patients with an initial diagnosis of DCIS on PCB had invasive disease on final pathology. In our study, the rate of SLN positivity among these upstaged patients was small but clinically significant (10%).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We found the upstage rate to invasive carcinoma to be 29%. This is consistent with the reported 8%‐40% upstage rate and corresponds with Brennan et al's meta‐analysis which found 26% (95% CI: 23%‐30%) of patients with an initial diagnosis of DCIS on PCB had invasive disease on final pathology. In our study, the rate of SLN positivity among these upstaged patients was small but clinically significant (10%).…”
Section: Resultssupporting
confidence: 91%
“…Other studies have demonstrated the utility of these preoperative markers of upstage risk . Multicentricity, patient reported symptoms and the presence of necrosis have also been reported as predictive factors; our study did not corroborate the significance of these additional findings. However, even without additional markers, our model consisting of palpability, disease on imaging greater than 1.20 cm and mass on pre‐op imaging significantly predicted upstaging in our population, with an overall positive predictive value (PPV) of 81%.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Notably, the proportion of SLN metastasis in DCIS patients undergoing SLN biopsy during breast surgery (breast conserving surgery or mastectomy) is reported to be 0.6-13.4% (6,8,(11)(12)(13)(14)(15)(16)(17). Given the low positivity and the potential harms the SLN procedure may cause, the role of SLN biopsy in most DCIS patients has been controversial in recent years (18).…”
Section: Introductionmentioning
confidence: 99%
“…To The Editor, I want to congratulate Dr. Watanabe et al for their study on the upstaging to invasive ductal carcinoma (IDC) after mastectomy for ductal carcinoma in situ (DCIS) [1]. They reported that 22.6% of 226 DCIS lesions were upgraded to IDC after mastectomy, and the prevalence of macrometastasis of sentinel lymph nodes (SLNs) was 0.9%.…”
mentioning
confidence: 99%